Receiver-based packet loss concealment for pulse code modulation (PCM G.711) coders. - Elsabrouty, Maha. (University of Ottawa (Canada), 2002)
Voice-over-IP (VoIP), the transmission of packetized voice over IP networks, is gaining much attention as a possible alternative to conventional Public Switched Telephone Networks (PSTN). However, impairments present on IP networks, namely jitter, delay and channel errors can lead to the loss of packets at the receiving end. This packet loss degrades the speech quality. Model-based coders, especially G.729-A and G.723.1 International Telecommunication Union (ITU-T) Standards, have been extensively used for speech coding over IP networks because of their inherent ability to recover from erasure. Their built-in packet loss concealment makes their quality drop slowly with increasing amount of packet loss. However, their memory makes the transition from the concealed state to the correct state require a few frames and they actually tend to corrupt a few good packets before recovery as a result of a phenomenon known as "State Error". On the other hand, Pulse Code Modulation (PCM), although having a higher score than G.729 and G.723 in the periods of normal operations, does not have the ability to conceal erasure and the quality of speech during loss periods drops dramatically. Yet it can recover from packet loss more rapidly than model-based coders since the first speech sample in the first good packet restores speech to its original quality. The goal of this work is to develop a Packet Loss Concealment (PLC) algorithm to provide the G.711 PCM coders with the required ability to conceal erasure and maintain a high score of user satisfaction. This algorithm uses a receiver-based prediction model to develop an estimate of the missing speech segments.
Keywords: Engineering, Electronics and Electrical.